PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN MAJENE - Akhsan HN; Saban Echdar; Fatmasari Fatmasari (Nobel Management Review, 2020)
The study aims to determine and analyze: 1) the direct influence of transformational leadership and work motivation on employee job satisfaction in the Majene Regency Regional Financial and Asset Agency, 2) the direct influence of transformational leadership and work motivation on employee performance in the Majene Regency Regional Finance and Asset Agency, and 3) the indirect effect of transformational leadership and work motivation on performance through employee job satisfaction at the Regional Finance and Assets Agency in Majene Regency This research design uses survey research. Location of the study was in the Regional Finance and Assets Agency in Majene Regency. The study was conducted from October to November 2019. The population in this study included all employees of the Majene Regency Financial and Asset Agency, amounting to 97 people. Sampling of this study was carried out using a saturated sampling technique (census), namely determining the entire population to be sampled as many as 97 employees of the Majene Regency Finance and Assets Agency. The data analysis technique used is path analysis. The results showed that: 1) there was a positive and significant direct effect on transformational leadership and work motivation on employee job satisfaction at the Financial and Asset Regional Agency of Majene Regency, 2) there was a positive and significant direct effect on transformational leadership and work motivation on employee performance in Regional Finance and Assets Agency of Majene Regency, and 3) there is a positive and significant influence indirectly on transformational leadership and work motivation on performance through employee job satisfaction at the Regional Finance and Asset Agency of Majene Regency